Structural study of three heteroaryl oximes, heteroaryl-N=OH: Compounds forming strong C3 molecular chains - Low, John Nicolson; Wardell, James Lewis; da Costa, Cristiane Franca; Souza, Marcus Vicinius Nora; Gomes, Ligia Rebelo (European Journal of Chemistry, 2018)
In order to further investigate the structural chemistry of oximes and to further establish the main structural arrangements adopted, we have determined the crystal structure of and carried out Hirshfeld surface calculations on three heteroaryl oximes, namely (Z)-thiophene-2-carbaldehyde oxime (1), (Z)-1H-pyrrole-2 carbaldehyde oxime (2) and (Z)-5-nitrofuran-2-carbaldehyde oxime (3). As confirmed by both techniques, the major intermolecular interactions in each compound are classical N—H···O hydrogen bonds, which link the molecules into C3 chains. Such an arrangement has been previous reported as an important aggregation mode for oximes. Secondary interactions, C—H···π and C—H···O interactions, in compounds 1 and 2, and interactions involving the nitro group oxygen atoms in compound 3 link the chains into three dimensional arrays.